Let:
x = Cost of one plain pizza
y = Cost of one soda
two friends went to a restaurant and ordered one plain pizza and two sodas. the bill totaled $15.95. so:
![\begin{gathered} x+2y=15.95_{\text{ }} \\ \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/j21gprmrzwvjqsf924cky6riintv763jm9.png)
later that day, five friends went to the same restaurant. they ordered 3 plain pizzas and 5 sodas. their bill totaled $45.90. so:
![3x+5y=45.90](https://img.qammunity.org/2023/formulas/mathematics/college/5dqkynnmzrt98lhfvmlma45ft9wwhmipbd.png)
Let:
![\begin{gathered} x+2y=15.95_{\text{ }}(1) \\ 3x+5y=45.90_{\text{ }}(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/iajh8m8oppy95sv5wmpdmdz10img8u43ia.png)
From (1) solve for x:
![x=15.95-2y_{\text{ }}(3)](https://img.qammunity.org/2023/formulas/mathematics/college/den2c1ibu4385aci9hwz8b3woqcy6tphfz.png)
Replace (3) into (2):
![\begin{gathered} 3(15.95-2y)+5y=45.90 \\ 47.85-6y+5y=45.90 \\ -y=-1.95 \\ y=1.95 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/c8rqadh32op2z92x73we6481d5bnnbi9tx.png)
Replace the value of y into (3):
![\begin{gathered} x=15.95-2(1.95) \\ x=12.05 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ky67wzpwr1ad6sut9sc95xi9laeweox9f3.png)
Therefore, the price of one plain pizza is $12.05